Results Of Using Compressed Alcohol In Vehicles (Eurasian Journal of Engineering and Technology, 2026)
Scientific and design work is being carried out on the use of alcohol in internal combustion engines instead of gasoline and liquefied gas (propane). According to the test results, the "Cobalt" vehicle’s acceleration time to 100 km/h when operating on compressed alcohol increased slightly to 11.75 sec (deteriorated) - [by 0.03 sec (0.26%) gasoline and 0.08 sec. (0.69%) propane], but in terms of CO content in exhaust gases, it completely decreased to 1.25% and met Euro-6 requirements [by 1.94% (2.03 times) gasoline and 2.57% (3.06 times) propane] and in terms of CH content up to 1.16% [by 2.51% (2.47 times) gasoline and 3.06% (3.64 times) propane].